Doppler velocimetry of normal human fetal venous intrapulmonary branches - Laudy, J. A. M.; Ursem, N. T. C.; Mulder, P. G. H.; Wladimiroff, J. W. (Ultrasound in obstetrics & gynecology, 1999)
Objectives To describe the nature of flow velocity wave‐forms from fetal middle and distal venous pulmonary branches in the second half of normal pregnancy in relation to gestation, and to test repeatability and interrelationships of flow velocity waveform recordings from proximal, middle and distal venous pulmonary branches. Design Cross‐sectional study. Subjects/methods A total of 111 normal singleton pregnancies between 20 and 40 weeks' gestation were studied using a color‐coded Doppler ultrasound system. Pulmonary waveforms were obtained at the level of the fetal cardiac four‐chamber view. Repeatability was tested from two recordings at 15‐min time intervals in 25 separate normal pregnancies. Results The nature of middle and distal venous pulmonary flow velocity waveforms was comparable with that of proximal waveforms. Acceptable repeatability of pulmonary venous flow velocity waveforms with coefficients of variation below 15% was established for nearly all velocity parameters and their ratios. A gestational age‐dependent change was found for all flow velocity waveform parameters including pulsatility index for veins at both middle and distal venous levels. Significant interpulmonary changes were observed for nearly all pulmonary venous waveform parameters. Conclusions It is speculated that increase in volume flow and venous pulmonary pressure gradient plays a role in gestational age‐dependent changes, whereas changes in vessel diameter and distance between the heart and more distal venous pulmonary vessels are responsible for interppulmonary changes. Copyright © 1999 International Society of Ultrasound in Obstetrics and Gynecology